2001
DOI: 10.1021/om010695s
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Interconversion between μ,η22- and μ3222-C60 on a Carbido Pentaosmium Cluster Framework

Abstract: Decarbonylation of Os 5 (CO) 14 (PPh 3 ) by 2 equiv of Me 3 NO/CH 3 CN at room temperature followed by reaction with C 60 in refluxing chlorobenzene produces Os 5 C(CO) 11 (PPh 3 )(µ 3 ,η 2 : η 2 :η 2 -C 60 ) (1) in 44% yield. Thermal treatment of 1 at 80 °C under 1 atm of carbon monoxide affords Os 5 C(CO) 12 (PPh 3 )(µ,η 2 :η 2 -C 60 ) (2) in good yield (72%). Upon thermolysis of 2 at 132 °C, 2 is cleanly reconverted to 1 (73%) by loss of a carbonyl ligand. Reaction of 1 with benzyl isocyanide at room temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…This new complex is one of the rare examples for a M-C 60 σ-bond. One further example, where C 60 can act as a four-electron ligand is the fullerene carbido pentaosmium cluster complex 28 shown in Scheme 7.13 [75,76]. Heating 26 with an excess of PPh 3 under pressure in chlorobenzene leads to the loss of one coordination site.…”
Section: Multinuclear Complexes Of C 60mentioning
confidence: 99%
See 1 more Smart Citation
“…This new complex is one of the rare examples for a M-C 60 σ-bond. One further example, where C 60 can act as a four-electron ligand is the fullerene carbido pentaosmium cluster complex 28 shown in Scheme 7.13 [75,76]. Heating 26 with an excess of PPh 3 under pressure in chlorobenzene leads to the loss of one coordination site.…”
Section: Multinuclear Complexes Of C 60mentioning
confidence: 99%
“…Such complexes are known for the clusters Os 5 C [75,76], Ru 5 C [77][78][79], Ru 6 C [78], PtRu 5 C [77] and Rh 6 [80]. Such complexes are known for the clusters Os 5 C [75,76], Ru 5 C [77][78][79], Ru 6 C [78], PtRu 5 C [77] and Rh 6 [80].…”
Section: Multinuclear Complexes Of C 60mentioning
confidence: 99%
“…Shapley et al [32][33][34] and Park et al [35][36][37][38][39] independently prepared various L n M x (C 60 ) y complexes and demonstrated that a variety of cluster frameworks [Re 3 (µ-H) 3 , Ru 3 , Os 3 , Ru 5 C, Os 5 C, PtRu 5 C, Ru 6 C, and Ru 6 ] can bind to C 60 through a face-capping cyclohexatriene-like bonding mode: µ 3 -η 2 ,η 2 ,η 2 -C 60 . The metallofullerene complexes with this relatively strong bonding mode exhibited remarkable thermal and electrochemical stabilities, uniquely suitable for various device applications, which is in contrast to other previously known η 2 -C 60 metal cluster complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In the carbon fullerene molecules, C 60 attracts one's attention by its excellent physical and chemical stability, and many investigations on its chemical, optical, and electronic properties have been published. [1][2][3][5][6][7] Now some theoretical work on the polarizability of C 60 fullerene under the external electric field has been carried out. For example, in Ref.…”
Section: Introductionmentioning
confidence: 99%